The Quality Of Student Argumentation is Determined By An Analysis Of Student Statements Viewed From Science Literature - Fitria Rahayu; Dini Meldiya Putri; Yoga Apriansyah; Ahmad Walid (Faculty of teaching training and education, 2022)
This study aims to evaluate junior high school students argumentative skills related to environmental contamination. This study employs a quantitative research methodology. The study was carried out at SMPN 14 Bengkulu City, in Padang Nangka, Singgaran Pati District, and the sample consisted of 26 class VII students who were chosen at random. The research tool was a descriptive (essay-style) test with five questions based on markers of argumentation skill (claims, data, warrants, backing, rebuttal, and qualifiers). An analysis was done based on the argumentative element in the student responses. According to the findings, 100% of students wrote claims, 19% wrote down data, 12% wrote warrants, 4% were able to write backings, and 0% wrote rebuttals and qualifiers. Overall, it can be said that most students can write claims, but they are starting to have trouble presenting data, warrants, backups, rebuttals, and qualifiers. Teachers can use the proportion of a student's initial reasoning skills as a benchmark to decide on designs or learning activities in the future that will not only focus on helping students understand topics but will also help them build or train their thinking skills.